2015
DOI: 10.1080/15476286.2015.1017220
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding regions ofC. elegansmRNA undergo selective adenosine to inosine deamination and contain a small number of editing sites per transcript

Abstract: ADARs (Adenosine deaminases that act on RNA) "edit" RNA by converting adenosines to inosines within doublestranded regions. The primary targets of ADARs are long duplexes present within noncoding regions of mRNAs, such as introns and 3 0 untranslated regions (UTRs). Because adenosine and inosine have different base-pairing properties, editing within these regions can alter splicing and recognition by small RNAs. However, despite numerous studies identifying multiple editing sites in these genomic regions, litt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
(84 reference statements)
0
16
0
Order By: Relevance
“…Thus, ADAR editing of RNA has sequence preferences, commonly referred to as nearest neighbors . Next‐generation sequencing studies have indicated that in most organisms, ADARs generally favor adenosines with a 5′ neighbor of uridine or cytidine and a 3′ neighbor of guanosine . However, there are slight differences in preferences between family members .…”
Section: Adar Recognition Of A‐to‐i Editing Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ADAR editing of RNA has sequence preferences, commonly referred to as nearest neighbors . Next‐generation sequencing studies have indicated that in most organisms, ADARs generally favor adenosines with a 5′ neighbor of uridine or cytidine and a 3′ neighbor of guanosine . However, there are slight differences in preferences between family members .…”
Section: Adar Recognition Of A‐to‐i Editing Substratesmentioning
confidence: 99%
“…Next‐generation sequencing studies have since revealed editing within Alu repeats located in noncoding regions of human mRNAs occurs at specific adenosines among different individuals . Furthermore, studies of 3′ UTRs in C. elegans revealed both editing patterns and that an editing event can affect the efficiency of editing at subsequent adenosines . Together, these studies suggest ADARs recognize specific adenosines in noncoding regions, indicating there may not be a difference in the mode of ADAR recognition of target adenosines between coding and noncoding regions.…”
Section: Adar Recognition Of A‐to‐i Editing Substratesmentioning
confidence: 99%
“…ADARs prefer an adenosine, uridine or cytidine 5 ′ of the target adenosine while guanosine is favored 3 ′ to the adenosine (Lehmann and Bass 2000;Eggington et al 2011;Bahn et al 2012;Bazak et al 2014). However, editing sites with the same surrounding nucleotide context can exhibit drastically different editing levels, suggesting this is not the only determinant of editing efficiency (Kawahara et al 2008;Tian et al 2011;Wheeler et al 2015). Alternative splicing of ADAR transcripts (Lai et al 1997;Rueter et al 1999) and post-transcriptional modification (Desterro et al 2005) have both been observed to cause decreased ADAR activity.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that ADR-1 does not edit RNA, but it can function to regulate the extent to which specific adenosines are edited by ADR-2 (Washburn et al 2014). In addition, we identified a novel C. elegans editing target, the mRNA Y75B8A.8, and characterized the pattern of editing events within its 3 ′ UTR (Wheeler et al 2015). As this 3 ′ UTR contains two highly edited sites, we utilized this gene to generate a reporter system to examine cis-and trans-acting factors that affect editing efficiency in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation